A single light : [large type] a novel - Lee, Tosca Moon (Center Point large print edition, 2019)
Six months after vanishing into an underground silo with sixty others, Wynter and Chase emerge to find the area abandoned. There is no sign of Noah and the rest of the group that was supposed to greet them when they emerged--the same people Wynter was counting on to help her locate the IV antibiotics her gravely ill friend, Julie, needs in order to live. As the clock ticks down on Julie's life, Wynter and Chase embark on a desperate search for medicine and answers. But what they find is not a nation on the cusp of recovery thanks to the promising new vaccine Wynter herself had a hand in creating, but one decimated by disease. What happened while they were underground? With food and water in limited supply and their own survival in question, Chase and Wynter must venture further and further from the silo. Aided by an enigmatic mute named Otto, they come face-to-face with a society radically changed by global pandemic, where communities scrabble to survive under rogue leaders and cities are war zones. As hope fades by the hour and Wynter learns the terrible truth of the last six months, she is called upon once again to help save the nation she no longer recognizes--a place so dark she's no longer sure it can even survive.